THE EVOLUTION OF STUDENTS MILITANCY IN A GLOBALIZING WORLD: TRENDS AND PATTERNS IN KENYA - Ngesu, Lewis Muli (IJRDO- Journal of Educational Research, 2017)
Student militancy as a widespread phenomenon in Africa, mainly since the 1960’s, is the subjectof a much older and wider “youth phenomenon” dating as far back as the middle ages, andspread widely across Europe in countries such as France, Italy, Germany and England, where themovement initially confined itself to the university campuses and centred on disobedience toauthority (for example, the king and his delegates) and on the refusal to be disciplined (Hobberin Lipest and Altbach, 1969: v, Ngesu 2013).Since the mid-1960’s and more intensively in the 1970’s nearly every Africa country had in oneway or another experienced a shake up by students outbreaks (Ishumi, 1976). Such countriesinclude Egypt, Senegal, Nigeria, Ghana, Cameroon, South Africa and Ethiopia. Again thetriggering causes varied and were frequently shaped by local situations but closer examinationreveals a basic struggle for “power’ to influence and/or actually participate in the affairs ofnational politics and education ranging from formulation of national goals and policies toformulation of school/college curricula to internal and external administration of the educationaland cultural institutions (Ishumi, 1976, Ngesu et al 2013). Closer home the first case of studentindiscipline was reported in Maseno in1908 when students refused to participate in manuallabour and pressed for more reading and writing (Anderson 1970, 135). Three years laterMumias School went on strike against colonial administration (Ngesu et al 2013).